Efficacy of Ginkgo biloba as an adjunct to donepezil in amyloid PET-positive Alzheimer’s patients - Yang, YoungSoon; Koo, Min-Seong; Kwak, Yong Tae (Frontiers in Neurology, 2025)
BackgroundGinkgo biloba is widely used in some regions as an adjunct therapy for Alzheimer’s disease (AD). Its potential mechanisms include antioxidative and anti-amyloid properties, yet clinical evidence remains mixed.ObjectiveWe investigated whether combining Ginkgo with donepezil confers additional benefits in amyloid PET-positive AD patients. We also explored changes in the plasma biomarker MDS-Oaβ (Multimer Detection System–Oligomeric Aβ), which reflects the propensity of Aβ monomers to form oligomers.MethodsThis retrospective study included newly diagnosed, drug-naïve AD patients who were amyloid PET-positive and had at least 12 months of follow-up. Participants received either donepezil alone (Donepezil-only) or donepezil plus Ginkgo (Donepezil-Ginkgo). Clinical measures included the Korean version of the Mini-Mental State Examination (K-MMSE) and the Sum of Boxes of the Clinical Dementia Rating (CDR-SB). Plasma MDS-Oaβ was assessed at baseline and at 12 months.ResultsA total of 101 patients were analyzed (60 Donepezil-only, 41 Donepezil-Ginkgo). Baseline demographics and clinical characteristics were similar. After 12 months, the Donepezil-only group showed minimal change in K-MMSE and a slight decrease in MDS-Oaβ. The Donepezil-Ginkgo group demonstrated a significant improvement in K-MMSE (+2.4) and a larger reduction in MDS-Oaβ (−0.15). No significant between-group difference was observed for CDR-SB. Adverse events were mostly mild and did not lead to discontinuation.ConclusionThe addition of Ginkgo to donepezil may yield superior cognitive outcomes and a greater decrease in plasma MDS-Oaβ compared with donepezil alone in amyloid PET-positive AD patients. Further large-scale, prospective trials are warranted to validate these findings and elucidate Ginkgo’s mechanistic role in AD.